Trading activity in public real estate markets - Thomas Richter (Journal of Risk and Financial Management, 2022)
Trading activity is an important characteristic of financial markets, since it is related to price discovery, volatility, and market liquidity. It is therefore of crucial importance to understand what drives trading activity in real estate markets. Here, we use a panel dataset consisting of 142 US REIT stocks observed over almost 20 years and a fixed-effects regression approach to link variation in trading activity to proxies for different trading motives (theory-motivated). The paper shows that the drivers of trading activity in real estate markets are distinct from those in the broader equity market. Proxies for portfolio rebalancing needs and liquidity trading are shown to be important trading motives in REIT markets. However, unlike in the broader equity market, difference of opinions and information-based trading motives seem to play a minor role for REIT trading activity.
Keywords: 650; public real estate; REITs; trading activity; trading motives